Roadside agroforestry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Landless villagers in North-west Bangladesh are using roadside verges and other wasteland areas for agroforestry. One kilometre of roadside plantation is giving villagers a net profit of about $200 per year. Proshika Manobik Unnayan Kendra, a...